2019
DOI: 10.1097/md.0000000000015191
|View full text |Cite
|
Sign up to set email alerts
|

Learning curve-cumulative summation analysis of visual estimation of left ventricular function in novice practitioners

Abstract: The aim of the present study was to determine the value of cumulative summation (CUSUM) analysis in assessing the proficiency of novice practitioners in estimating the left ventricular ejection fraction (EF). Seven novice practitioners with no echocardiography experience were recruited in this observational study. Each practitioner assessed EF from echocardiographic video files of 100 cases, one by one, and received feedback and teaching. We obtained a CUSUM score through comparison of the gold stan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Akinboboye et al proposed that an acceptable learning curve of visual estimation of LVEF occurred after 20 cases had been reviewed with instant feedback [ 22 ]. In comparison, Lee et al reported a minimum of 55 case reviews with feedback to effectively train LVEF visual estimation in medical students [ 23 ]. This study used 35 cases with instant feedback because our objective was to evaluate the ability to estimate the LVEF rather than training.…”
Section: Discussionmentioning
confidence: 99%
“…Akinboboye et al proposed that an acceptable learning curve of visual estimation of LVEF occurred after 20 cases had been reviewed with instant feedback [ 22 ]. In comparison, Lee et al reported a minimum of 55 case reviews with feedback to effectively train LVEF visual estimation in medical students [ 23 ]. This study used 35 cases with instant feedback because our objective was to evaluate the ability to estimate the LVEF rather than training.…”
Section: Discussionmentioning
confidence: 99%
“…There appear to be no other reported uses of sequential testing being employed in FCU competence assessment in this manner. One study ( 20 ) in which novice practitioners watched cine loops of varying LV function demonstrated approximately 50 cases with feedback were required to become “proficient” at eyeballing ejection fraction. Again, using sequential analysis, variability in the numbers of cine loops that each novice practitioner required was shown, ranging from 40 to 71 cases.…”
Section: Discussionmentioning
confidence: 99%
“…Beside that, long-term retention was not assessed and thus the durability of the improvement in precise measurement of left ventricular ejection fraction cannot be assessed in this study. Therefore, the improvement shown in our present data may be lost over time [28].…”
Section: Discussionmentioning
confidence: 99%